2017
DOI: 10.4103/jcd.jcd_311_16
|View full text |Cite
|
Sign up to set email alerts
|

A novel technique of sculpting Biodentine in the restoration of iatrogenic dentin loss

Abstract: Excessive tooth structure loss is a common iatrogenic error encountered during endodontic practice. Conservative treatment planning is essential to maintain the structural integrity in such teeth. This case report elucidates a novel approach in sculpting Biodentine as a dentin substitute followed by internal bleaching and restoration with fiber-reinforced composite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…Biodentine is the preferred material, especially for endodontic repair. [ 1 2 3 ] It is reported that root canal irrigants encounter biomaterials used for repair, affect the biomaterial, and modify its surface characteristics and microhardness. [ 5 6 ] A material’s surface strength can be estimated from its surface microhardness, and Vickers hardness has been used as an indicator for evaluating the strength of calcium silicate-based materials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biodentine is the preferred material, especially for endodontic repair. [ 1 2 3 ] It is reported that root canal irrigants encounter biomaterials used for repair, affect the biomaterial, and modify its surface characteristics and microhardness. [ 5 6 ] A material’s surface strength can be estimated from its surface microhardness, and Vickers hardness has been used as an indicator for evaluating the strength of calcium silicate-based materials.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to their inherent hydraulic characteristics, they set in the presence of blood and surrounding tissue fluids. [ 1 ] Tricalcium silicate-based cement Biodentine has been developed and used for various clinical applications such as mineral trioxide aggregate (MTA). [ 2 ] The powder components of Biodentine are zirconium oxide, calcium carbonate, and tricalcium silicate, and a liquid part containing calcium chloride acts as a water water-reducing agent as well as an accelerator.…”
Section: Introductionmentioning
confidence: 99%
“…Hand pluggers were used to carefully compact the Biodentine over collagen barricade, and an apical plug of 5 mm of Biodentine was formed. Similarly, Biodentine was adapted along the lateral walls of the root canal using the circumferential uncovering technique[ 3 ] using hand pluggers. Once the setting of Biodentine was confirmed, it was etched with 37% phosphoric acid, rinsed and bonding agent was applied.…”
Section: Discussionmentioning
confidence: 99%
“…Biodentine (Septodont, St. Maur des Fosses, France) was also compacted along the lateral walls of the root canal with the help of hand pluggers to increase its thickness using the circumferential uncovering technique [ Figure 1c ]. [ 3 ] After Biodentine had completely set, the canal walls were etched with 37% phosphoric acid (MD-Chelcream, Meta Biomed, Korea), rinsed with water, followed by application of bonding agent (Prime and Bond, Dentsply Sirona, USA). Glass fiber post (Glassix, Nordin-Dental, Switzerland) was used to obturate the canal using resin luting cement (RelyX, 3M ESPE, USA), and coronal restoration was carried out with composite restoration (Tetric N-Ceram, Ivoclar Vivadent, Germany) [Figure 1d and e ].…”
Section: Case Reportmentioning
confidence: 99%
“…Biodentine™ is a promising restorative material (increased compressive strength, pushout bond strength, density, and porosity), offering a lower cost and better handling properties, allowing it to be sculpted into a desired form within the adequate setting time. It also possesses high wash out, low fluid uptake and resorption values, as well as superior mechanical properties [23]. However, Biodentine™ does not satisfy the requirements to be used as an ideal core material [24].…”
Section: Biodentine™ -Composition and Propertiesmentioning
confidence: 99%